Inquiry-based learning: an effective approach to teaching science aiming to develop students’ competencies - Linh Thi Ngoc Bui; Vu Thuan Khuu (Vietnam Journal of Education, 2020)
Competency-based learning is among major changes of 2018 in Vietnam’s school curriculum, where teaching and learning aim to help school students develop core qualities and competencies in order to be successful in school, life, and prospective workplace. As this educational approach is relatively unfamiliar to Vietnamese teachers, they may feel confused about appropriate teaching strategies allowing them to obtain the new teaching goals. This would be the case when teachers have to teach integrated subjects such as Science in lower-secondary education. This paper will elaborate why inquiry-based instruction could be an effective approach that enables secondary teachers to accomplish their professional work in terms of facilitating their students to develop core competencies and those in Science. Some recommendations on teacher education and training will be made to enhance the successful implementation of inquiry-based teaching in Vietnamese classrooms.